Rapid Refrigeration and Water Protection Next Generation Adsorbents - Das, Rasel; Saha, Bidyut Baran (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides a cross-disciplinary, multi-scale assessment of the development of adsorption-based refrigerants and super-adsorbent-based wastewater purification. The book covers two major aspects from the 21st century, including the development of an environmentally benign adsorption cooling system and the preparation of a super-adsorbent for water purification. Although work has been published on these topics, the authors present the latest findings and introduce some new perspectives. The book is written as a reference book with contributions from global field experts and will appeal to water engineers, chemists, environmentalists, physicists, material scientists, nano-technologists, and environmental technologists.
Chapter 1 Introduction -- Chapter 2 Towards the Development of Compact and High Efficiency Adsorption Heat Pumps -- Chapter 3 Synthesis and Characterization of Various MOFs and MOFs-Zeolite Com-posites: Water Adsorption and Rapid Cooling Production -- Chapter 4 Specific Heat Capacity of Carbon-based Composites for Adsorption Heat Pump and Desalination Applications -- Chapter 5 Characterizing Adsorbent Materials Employing Atomic Force Microscopy -- Chapter 6 Advanced Adsorbents for Ecological Applications: Water Harvesting from the Atmosphere and Recuperation Heat and Moisture in Ventilation Systems -- Chapter 7 Thermochemical Conversion of Lignocellulosic Waste to Activated Carbon: A Potential Resource for Industrial Wastewater Treatment -- Chapter 8 Carbon Nanomaterial-based Adsorbents for Water Protection -- Chapter 9 Nanoparticles-based Adsorbents for Water Pollutants Removal.
Keywords: Pollution; Water; Hydrology; Environment; Environmental chemistry; Chemistry, Technical; Nanotechnology; Pollution; Water; Environmental Sciences; Environmental Chemistry; Industrial Chemistry; Nanotechnology